Transatlantic Cooperation Surrounding Health Related Information and Communication Technology - De Moor, Georges J. E. (Studies in health technology and informatics ;, 2011)
A Memorandum of Understanding (MoU) on Cooperation Surrounding Health Related Information and Communication Technologies (ITC) was signed in Washington DC on December 17, 2010 between the EU and the US. This high-level partnership sent a strong signal to all stakeholders that a more global approach was needed to foster mutual understanding of the opportunities and challenges ahead, and reinforced the belief that advancing the effective use of Health ICT will benefit patients, health systems and the eHealth market. This book introduces the Policy Briefs which have resulted from the ARGOS project.